Foetal blood flow measured using phase contrast cardiovascular magnetic resonance – preliminary data comparing 1.5 T with 3.0 T - Tsai-Goodman, Beverly (J Cardiovasc Magn Reson, 2015)
BACKGROUND: Phase contrast cardiovascular magnetic resonance (PC CMR) has emerged as a clinical tool for blood flow quantification but its use in the foetus has been hampered by the need for gating with the foetal heart beat. The previously described metric optimized gating (MOG) technique has been successfully used to measure foetal blood flow in late gestation foetuses on a 1.5 T CMR magnet. However, there is increasing interest in performing foetal cardiac imaging using 3.0 T CMR. We describe our pilot investigation of foetal blood flow measured using 3.0 T CMR. METHODS: Foetal blood flows were quantified in 5 subjects at late gestational age (35–38 weeks). Three were normal pregnancies and two were pregnancies with ventricular size discrepancy. Data were obtained at 1.5 T and 3.0 T using a previously described PC CMR protocol. After reconstruction using MOG, blood flow was quantified independently by two observers. Intra- and inter-observer reproducibility of flow measurements at the two field strengths was assessed by Pearson correlation coefficient (R(2)), linear regression and Bland Altman analysis. RESULTS: PC CMR flow measurements were obtained in 36 of 40 target vessels. Strong intra-observer agreement was obtained between measurements at each field strength (R(2) = 0.78, slope = 0.83 ± 0.11), with a mean bias of −1 ml/min/kg and 95% confidence limits of ±71 ml/min/kg. Inter-observer agreement was similarly high for measurements at both 1.5 T (R(2) = 0.86, slope = 0.95 ± 0.13, bias = 6 ± 52 ml/min/kg) and 3.0 T (R(2) = 0.88, slope = 0.94 ± 0.13, bias = 4 ± 47 ml/min/kg). Across all PC CMR measurements, SNR per pixel was expectedly higher at 3.0 T relative to 1.5 T (165 ± 50%). The relative differences in flow measurements between observers were low (range: 4–16%) except for pulmonary blood flow which showed much higher variability at 1.5 T (34%) versus that at 3.0 T (11%). This was attributed to the poorly visualized, small pulmonary vessels at 1.5 T, which made delineation inconsistent between observers. CONCLUSIONS: This is the first pilot study to measure foetal blood flow using PC CMR at 3.0 T. The flow data obtained were in good correlation with those measured at 1.5 T, both within and between observers. With increased SNR at 3.0 T, smaller pulmonary vessels were better visualized which improved inter-observer agreement of associated flows. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12968-015-0132-2) contains supplementary material, which is available to authorized users.